Identifikasi Kandungan Rhodamin B Pada Blush On Dengan Metode Analisis Kualitatif Dan Kuantitatif Menggunakan Spektrofotometri Uv-Vis - Amanah, Nurul; Raihanah, Raihanah; Adellia, Ocvrisia; Ardisya, Pinky Alifanda; Elliza, Putri; Pratama, Rahmad; Oktavia, Regina (LPPM Universitas Sari Mulia, 2025)
Background: Cosmetics are one of the basic necessities for mankind, especially for women. Where its presence is very necessary for many women to beautify themselves and enhance their appearance. Objective: to find out whether the blush on the market in South Kalimantan uses Rhodamine B dye Method: qualitative analysis was carried out using staining, then continued with quantitative analysis using UV-Vis spectrophotometry Results: The quantitative results obtained for sample A were 18,699mg/L, for sample B 1,942 mg/L. Conclusion: From the results of quantitative and qualitative tests, it was found that sample A was positive for containing rhodamine B and sample B was negative for containing rhodamine B. From these results, sample A was declared very dangerous for consumers because it contained textile dyes. The greater the possibility that rhodamine B entering the body will have toxic effects, respiratory problems and skin disorders. Keywords: Rhodamine B, Blush On, Cosmetics.